Respiratory Care In The Icu: Key Nursing Interventions" (Journal of Namibian Studies : History Politics Culture, 2022)
Respiratory care in the intensive care unit (ICU) demands meticulous attention and expert intervention from nursing staff to ensure optimal patient outcomes. This article delineates key nursing interventions essential for effective respiratory management in critically ill patients. Beginning with an overview of common respiratory conditions encountered in the ICU, emphasis is placed on the importance of thorough respiratory assessment and early recognition of distress signs. Ventilator management, airway clearance techniques, and oxygen therapy administration are discussed in detail, highlighting nursing responsibilities in ensuring patient safety and comfort. Furthermore, the significance of patient and family education, multidisciplinary collaboration, and effective communication strategies is underscored. Through a holistic approach encompassing assessment, intervention, education, and collaboration, nurses play a pivotal role in promoting respiratory health and optimizing outcomes for ICU patients.